Legal aspects in tourism and hospitality - Bascos, Melinda (Manila, Philippines : Edric Publishing House, 2020)
The tourism and hospitality industry operates within a comprehensive domestic and international, legal and regulatory framework.
CHAPTER 1. Law of hospitality -- 2. Business Organizations and partnerships -- 3. Consumer's Law -- 4. Consumer's right, protection and product liability -- 5. Consumer contract law -- 6. Law of carriers and Inns -- 7. Travel Agents -- 8. Travel law -- 9. Travel Insurance Law -- 10. Tour operators and agency -- 11. Liquor law -- 12. Catering Services -- 13. Marketing law -- 14. Gaming Law -- 15. Payments systems -- 16. Visa law -- 17. Law of bailment
Includes bibliographical references.
Keywords: HOSPITALITY INDUSTRY -- LAW AND LEGISLATION